John Putnam Merrill: the unsung Hero behind the first successful renal transplantation - Abdi, Reza (Frontiers in Transplantation, 2025)
The first successful renal transplantation, performed between the Herrick twins at Peter Bent Brigham Hospital (PBBH) in 1954, was the culmination of four decades of collaboration among an exceptional group of physician-scientists and hospital leadership. PBBH was built with the primary goal of establishing an institution dedicated to biomedical research. John Merrill, a cardiologist who would go on to lay the foundation of modern nephrology, was perhaps one of the most important leaders in this effort. In addition to his pioneering transplantation work, Merrill developed what became the first functional dialysis machine that played a crucial role in stabilizing the diseased Herrick twin brother in preparation for the transplantation surgery—an operation that would go down in history as the world's first successful organ transplantation. Through these collective efforts, PBBH became the only hospital in the world at the time capable of offering a lifesaving dialysis-transplant procedure that combined both groundbreaking interventions. The dialysis-to-transplant model developed by Merrill has subsequently been adopted worldwide and saved thousands of lives.